Multimedia and the Management of Open and Distance Learning for Teacher Education in Nigerian Universities - Alabi, A. T.; Etejere, P. A. O.; Onasanya, S. A. (International Journal of Educational Management, 2022)
In recent times, open and distance learning for teacher education has been a major concept of discourse. The application of instructional multimedia system design approach has further brought substantial amount of success in designing, implementing and evaluating the process of open and distance learning for online delivery. This article explores the benefits of the principles of integrated model of multimedia in open and distance learning for teacher education in Nigerian Universities. The management challenges characterized by planning, staffing, training, and funding of, as well as constraints in the effective use of Information and Communication Technology in, open and distance learning were discussed. Recommendations for effective delivery within the purview of open and distance learning for teacher education in Nigerian universities made included, among others, organizing relevant course writing workshops and retreats for ODL modules, training learners and instructors on effective and appropriate use of multimedia techniques as well as recognizing the materials developed by the instructors as academic publications for staff appraisal purposes.